Overview of KAGRA: Calibration, detector characterization, physical environmental monitors, and the geophysics interferometer. (22nd February 2021) - Akutsu, T; Ando, M; Arai, K; Arai, Y; Araki, S; Araya, A; Aritomi, N; Asada, H; Aso, Y; Bae, S; Bae, Y; Baiotti, L; et al.
Abstract: KAGRA is a newly built gravitational wave observatory, a laser interferometer with a 3 km arm length, located at Kamioka, Gifu, Japan. In this series of articles we present an overview of the baseline KAGRA, for which we finished installing the designed configuration in 2019. This article describes the method of calibration (CAL) used for reconstructing gravitational wave signals from the detector outputs, as well as the characterization of the detector (DET). We also review the physical environmental monitoring (PEM) system and the geophysics interferometer (GIF). Both are used for characterizing and evaluating the data quality of the gravitational wave channel. They play important roles in utilizing the detector output for gravitational wave searches. These characterization investigations will be even more important in the near future, once gravitational wave detection has been achieved, and in using KAGRA in the gravitational wave astronomy era.